PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN NUSANTARA DI KEBUN RAYA BOGOR : Survey pada wisatawan nusantara individu di kebun raya bogor - Ristina, Geni Sopa (2014)
Bogor Botanical Gardens is one of the plant conservation centers which functioned also as a tourist destination areas in the city of Bogor, the category of tourists who visit them, individual tourists and groups, individuals and groups of foreign travelers, from year to year the number of visitors is increasing Bogor Botanical Garden , the Bogor Botanical Gardens every year always target level of tourist arrivals must always experience an increase in every year, but in the year 2012 to the year of 2013 losing decrease in the number of tourists visiting the individual. This is because many competitors like many other tourist attractions in the city of Bogor, in an effort to increase the level of domestic tourists visiting individual travelers to make the word of mouth (word of mouth promotion) consisting of talkers, topicks, tools, taking parts, and tracking. This study aims to describe the word of mouth and the decision of tourists visiting word of motuh influence on the decision to visit. The research used is desktiptif and verification methods used explanatory survey. The samples in this study were 100 respondents that individual tourists who visit the Garden with the sampling techniques used are unsaturated samples. The data analysis technique used is multiple regression. Independent variables in this study are talkers (X1), topicks (X2), tools (X3), taking parts (X4) and tracking (X5) while the dependent variable is the decision to visit (Y) which is comprised of product selection, brand selection, selection distributor, the timing of the visit and the selection of the number of visits. The results showed that the response to word of mouth travelers to visit the highly rated decisions. Factor that is highly rated by the talkers, while taking parts to obtain low valuation. The response to the decision of individual tourists visiting the highest assessment medapat dealer elections. While obtaining the lowest score is the selection of the brand. Based on SPSS 18 showing testing the influence of the simultaneous and partial between word of mouth by making a visit. As for advice to companies is to improve communication with tourists thereby increasing the intensity of word of mouth between the sender (information providers) to receiver (recipient information) so that tourists will be attracted to visit Bogor Botanical Garden.